2021
DOI: 10.1098/rstb.2020.0379
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and plant reproduction: trends and drivers of mast seeding change

Abstract: Climate change is reshaping global vegetation through its impacts on plant mortality, but recruitment creates the next generation of plants and will determine the structure and composition of future communities. Recruitment depends on mean seed production, but also on the interannual variability and among-plant synchrony in seed production, the phenomenon known as mast seeding. Thus, predicting the long-term response of global vegetation dynamics to climate change requires understanding the response of masting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 109 publications
(193 reference statements)
0
38
0
Order By: Relevance
“…Thus while we detected no broad patterns in CVp across regions, more localized patterns may exist within species [26,64]. In addition, increasing data collection across elevational gradients at different latitudes in mountainous areas will allow for documenting mast-seeding patterns over time and testing hypotheses related to climate change (see also [34]). While temperature increases are predicted to be substantial at high latitudes, other components of climate change include frequency and severity of fires, insect attacks and extreme weather events [65], and increasing CO 2 has been shown to experimentally impact conifer seed production [66] and could impact long-term mast-seeding patterns.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Thus while we detected no broad patterns in CVp across regions, more localized patterns may exist within species [26,64]. In addition, increasing data collection across elevational gradients at different latitudes in mountainous areas will allow for documenting mast-seeding patterns over time and testing hypotheses related to climate change (see also [34]). While temperature increases are predicted to be substantial at high latitudes, other components of climate change include frequency and severity of fires, insect attacks and extreme weather events [65], and increasing CO 2 has been shown to experimentally impact conifer seed production [66] and could impact long-term mast-seeding patterns.…”
Section: Discussionmentioning
confidence: 77%
“…Whether absolute temperature values (T) or relative temperature compared to the previous year (ΔT ) drive reproduction is critical to forecasting future mast events under a warming climate; if ΔT is the main driver then mast-seeding variability is not expected to change [21], whereas direct climate warming would lead to an increased cueing frequency that may induce a breakdown in mast-seeding patterns over time [32]. While temperature appears to play a key role, the depletion of endogenous resources by a large reproductive event diminishes the number of reproductive buds the following year even when the conditions are favourable, such that high levels of reproduction do not happen in consecutive years [26,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…This could shift the beech-rodent interactions towards antagonism, with higher rodent abundances (predicted also by [90]), more seed consumed and fewer cached (recall that caching declines with more frequent masting: figure 3). On the other hand, a recent meta-analysis of global data suggests that masting has become more pronounced ( [91]; see also [92]). Such a change could make seed caching more profitable for granivores (higher intensity of masting promotes caching: figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…[68,69]). In newly established forests, or those recovering from disturbance, ontogenetic changes in masting will have important implications for management [5], irrespective of any parallel changes in masting resulting from environmental change [35].…”
Section: (B) Ontogenymentioning
confidence: 99%
“…Resource dynamics, environmental variation, genetic and hormonal regulation, pollen limitation and their alignment through space and time are factors that generate variability and synchrony [3]. The specific way each of these proximate factors drives masting is highly variable among plant species and even populations [46], providing an exciting avenue for research but also creating a challenge in predicting the responses of masting to climate change [35]. For example, LaMontagne et al [36] found that in North America conifers, masting is cued by the difference between summer temperatures 2 and 3 years before seed fall, supporting the so-called ΔT model (i.e.…”
Section: (A) Proximate Mechanismsmentioning
confidence: 99%